﻿ GreeneMath.com - Properties of Addition Test

In our lesson, we learned a few valuable properties of addition. The commutative property of addition shows us that we can change the order without changing the sum. The associative property of addition shows us that we can change the grouping without changing the sum.

Test Objectives:

•Demonstrate the ability to rewrite a sum using the commutative and associative properties

•Demonstrate the ability to identify the parts of an addition problem as addend or sum

•Demonstrate the ability to add using the identity property of zero

#1:

Instructions: Rewrite each using the commutative property.

a) 1 + 7

b) 2 + 4

c) 6 + 15

d) 13 + 12

Watch the Step by Step Video Solution
|
View the Written Solution

#2:

Instructions: Rewrite each using the commutative property.

a) 21 + 1

b) 13 + 9

c) 51 + 7

d) 103 + 2

Watch the Step by Step Video Solution
|
View the Written Solution

#3:

Instructions: Identify the parts of each addition problem.

a) 9 + 4 = 13

b) 12 + 10 = 22

c) 5 + 4 + 11 + 3 = 23

Instructions: Find each sum.

d) 37 + 0

e) 962 + 0

f) 1,362,373 + 0

Watch the Step by Step Video Solution
|
View the Written Solution

#4:

Instructions: Rewrite each using the associative property.

a) (3 + 1) + 5

b) 17 + (11 + 2)

c) (9 + 2) + 1

Watch the Step by Step Video Solution
|
View the Written Solution

#5:

Instructions: Rewrite each using the associative property.

a) (4 + 6) + 7

b) 13 + (2 + 8)

c) (10 + 20) + 15

Watch the Step by Step Video Solution
|
View the Written Solution

Written Solutions:

#1:

Solution:

a) 1 + 7 = 7 + 1

b) 2 + 4 = 4 + 2

c) 6 + 15 = 15 + 6

d) 13 + 12 = 12 + 13

Watch the Step by Step Video Solution

#2:

Solution:

a) 21 + 1 = 1 + 21

b) 13 + 9 = 9 + 13

c) 51 + 7 = 7 + 51

d) 103 + 2 = 2 + 103

Watch the Step by Step Video Solution

#3:

Solution:

d) 37 + 0 = 37

e) 962 + 0 = 962

f) 1,362,373 + 0 = 1,362,373

Watch the Step by Step Video Solution

#4:

Solution:

a) (3 + 1) + 5 = 3 + (1 + 5)

b) 17 + (11 + 2) = (17 + 11) + 2

c) (9 + 2) + 1 = 9 + (2 + 1)

Watch the Step by Step Video Solution

#5:

Solution:

a) (4 + 6) + 7 = 4 + (6 + 7)

b) 13 + (2 + 8) = (13 + 2) + 8

c) (10 + 20) + 15 = 10 + (20 + 15)

Watch the Step by Step Video Solution